Enhancing AICCRA’s Impact in Ethiopia through Feed and Forage Research and Scaling Innovations - Mekonnen, Kindu; Gebreyes, Million (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
- Over 31,900 smallholder farmers benefited from feed and forage interventions across North Shewa, Hadiya, Kembata, Siltie, and Guraghe zones, with 23–25% being women farmers. - A total of 998 farmers, development agents, and experts received theoretical and practical training on feed and forage production, management, utilization, and seed systems. - Scaling challenges include limited access to certified seeds, land scarcity, weak market linkages, high input costs, inadequate coordination, policy gaps, lack of monitoring tools, and insufficient resource allocation. - Planned actions focus on expanding forage seed commercialization models, collecting cost-benefit evidence, mapping priority forage species, and sharing lessons from scaling initiatives.